Peningkatan Kesejahteraan Psikologis Wanita Menikah dengan Gangguan Fertilitas Idiopatik melalui Terapi Narima Ing Pandum - Astrini Arimurti Suhita; Subandi Subandi (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
Conceiving a child in marriage is one factor that influencing well-being.  The inability to have a child means to pressure and suffering for the couple, especially toward women with idiopathic infertility. This study aimed to investigate the influence of Narima Ing Pandum (NIP) therapy. NIP was developed based on Javanese values of sabar (patience), syukur (gratitude) and narima (acceptance). This study used a single case A-B-A design. Psychological well-being and NIP measured using NIP checklist and psychological well-being checklist. Visual inspection and descriptive analysis were used. The result indicated that NIP therapy increased the psychological well being of married women with idiopathic infertility, marked by the increasing of NIP values of the two participants.